Effect of Income Diversification on Poverty Reduction and Income Inequality in Rural Nigeria: Evidence from Rice Farming Households - Awotide, B.A.; Awoyemi, T.T.; Diagne, A.; Kinkingnihoun, F.M.; Ojehomone, V. (2012)
The desire to increase household income and insure against agricultural production risk has led rural households to increasingly diversify their income sources. Yet the potential roles of income diversification on poverty reduction particularly among the rural farmers have not been adequately examined in Nigeria. Therefore, in order to fill this gap and complement other studies on income diversification, this study examined the effect of income diversification on poverty reduction among the rice farming households in Nigeria. Using the primary data collected from 600 randomly selected smallholder rice farmers in Nigeria and adopting the Foster-Greer-Thorbecke (FGT) poverty measures the study observed that farmers that participated in Non-Farm Wage Employment (NFWE) were better off than those in the Farm Related Employment (FRE) and the Non-Farm Self Employment (NFSE). The findings of this study revealed that diversification of income should be given more focus and attention by policy makers in the efforts to reduce poverty among smallholder farmers in rural Nigeria. Farmers should be encouraged to participate more in farmers' organization, the issue of access to land in the rural areas should be thoroughly examined and gender equity in access to productive resources should also be looked into.